2023
DOI: 10.1083/jcb.201911062
|View full text |Cite
|
Sign up to set email alerts
|

Septin-mediated RhoA activation engages the exocyst complex to recruit the cilium transition zone

Abstract: Septins are filamentous GTPases that play important but poorly characterized roles in ciliogenesis. Here, we show that SEPTIN9 regulates RhoA signaling at the base of cilia by binding and activating the RhoA guanine nucleotide exchange factor, ARHGEF18. GTP-RhoA is known to activate the membrane targeting exocyst complex, and suppression of SEPTIN9 causes disruption of ciliogenesis and mislocalization of an exocyst subunit, SEC8. Using basal body-targeted proteins, we show that upregulating RhoA signaling at t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Septins also regulate RhoA activity and actin polymerization facilitating trafficking of ciliary cargo proteins ( 13 ). For example, SEPTIN9 enhances the activity of ARHGEF18, which in turn activates RhoA ( 115 ). In this context, activated RhoA is required for the assembly of the complete exocyst complex ( 116 ), which orchestrates transport of post-Golgi vesicles containing transition zone proteins of the NPHP and MKS complexes ( 115 , 117 ).…”
Section: Molecular Determinants Of Actin Regulation At the Primary Ci...mentioning
confidence: 99%
“…Septins also regulate RhoA activity and actin polymerization facilitating trafficking of ciliary cargo proteins ( 13 ). For example, SEPTIN9 enhances the activity of ARHGEF18, which in turn activates RhoA ( 115 ). In this context, activated RhoA is required for the assembly of the complete exocyst complex ( 116 ), which orchestrates transport of post-Golgi vesicles containing transition zone proteins of the NPHP and MKS complexes ( 115 , 117 ).…”
Section: Molecular Determinants Of Actin Regulation At the Primary Ci...mentioning
confidence: 99%
“…All in all this reveals that ciliary septin function requires septin basic building blocks (SEPT7), relies on octamers (SEPT9) and suggests that septins form filaments. Yet, septin-related extra ciliary functions for example in vesicle transport (10,18,19) might also influence cilia number and length. However, these results corroborate previous studies that have assigned an important role in ciliogenesis to the septin cytoskeleton (5)(6)(7)20).…”
Section: Septins Localize To Ciliamentioning
confidence: 99%
“…Recently, it was shown that SEPT9 regulates the recruitment of transition zone proteins on Golgi-derived vesicles by activating the exocyst via the ARHGEF18 and RhoA (10). Most studies concur that inhibition of septins by any means results in less formation of cilia (5,6,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations